A cost-effectiveness analysis of calcipotriol plus betamethasone dipropionate aerosol foam versus gel for the topical treatment of plaque psoriasis. (3rd July 2018) - Foley, Peter; Garrett, Sinead; Ryttig, Lasse
Abstract: Background: Calcipotriol 50 µg/g and betamethasone 0.5 mg/g dipropionate (Cal/BD) aerosol foam formulation provides greater effectiveness and improved patient preference compared with traditional Cal/BD formulations for the topical treatment of plaque psoriasis. Objective: To determine the cost-effectiveness of Cal/BD foam compared with Cal/BD gel from the Australian perspective. Methods: A Markov model was developed to evaluate the cost-effectiveness of topical Cal/BD foam and gel for the treatment of people with plaque psoriasis. Treatment effectiveness, safety, and utilities were based on a randomized control trial, resource use was informed by expert opinion, and unit costs were obtained from public sources. Outcomes were reported in terms of 1-year costs, quality-adjusted life years, and incremental cost-effectiveness ratios. All costs were reported in 2017 Australian Dollars. Results: The model showed that patients using Cal/BD foam had more QALYs and higher costs over 1 year compared with patients using Cal/BD gel, resulting in a cost of 13, 609 per QALY gained at 4-weeks. When 4 weeks of Cal/BD foam was compared with 8 weeks of Cal/BD gel treatment, Cal/BD foam was 8 less expensive and resulted in 0.006 more QALYs gained. Sensitivity analyses showed that, compared with Cal/BD ointment, Cal/BD foam was associated with an incremental cost of 15, 091 per QALY gained. Conclusion: Cal/BD foam is the most cost-effective Cal/BD formulation for the topical treatment of patients with plaque psoriasis.